Peran dan Penerapan Komunikasi Asertif Orang Tua dalam Melakukan Pola Asuh Kepada Anak - Ilyas Naufal Zuhdi; Ana Kuswanti (Universitas Islam Lamongan, 2023)
The phenomenon of communication within the family often involves authoritarian attitudes of parents towards their children. There is an emphasis on parental demands and interventions that must be obeyed by the child. Strong parental interventions can cause children to feel afraid to express their true feelings and desires. This research aims to investigate the role of parents in applying assertive communication through parenting to their children. The theory used in this study is the self-disclosure theory, which explains that self-disclosure is the process where a child dares to share information, thoughts, feelings, or experiences with their parents. The research method employed is qualitative descriptive, with data collection conducted through a literature study. The gathered information is then developed. The results showed that the application of assertive communication in the family is very important to form a healthy and harmonious relationship. Assertive communication supports balanced authoritative parenting, promoting positive growth and development for each family member.